2021
DOI: 10.3390/ijerph182412942
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Plantar Pressure Distribution and Rearfoot Alignment in the Taiwanese College Athletes with Plantar Fasciopathy during Static Standing and Walking

Abstract: Background: Plantar fasciopathy (PF) is usually related to changes in foot arch, foot shape and rearfoot posture. However, little research has been implemented by using large-scale datasets, and even less has been conducted centering on plantar pressure distributions (PPDs) of different genders of PF athletes. This study aimed to investigate the relationships among the arch index (AI), the PPDs and the rearfoot postural alignment in hundreds of college athletes with PF during static standing and walking. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…Apart from this, the hemiplegic CP students in this study presented a most common feature of increased plantar load on the medial aspect of the foot, accompanied by a rearfoot valgus posture on the hemiplegic foot. The feature appeared to constitute the pronated foot characteristics, and such results were consistent with previous studies that suggested bearing a lower medial longitudinal arch contributes to the incidence of rearfoot pronation and thus increased plantar load on the medial aspect of the rearfoot [ 32 , 50 , 51 ]. Rearfoot valgus associated with a pronated foot often significantly increases the possibility of extensive foot pain [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Apart from this, the hemiplegic CP students in this study presented a most common feature of increased plantar load on the medial aspect of the foot, accompanied by a rearfoot valgus posture on the hemiplegic foot. The feature appeared to constitute the pronated foot characteristics, and such results were consistent with previous studies that suggested bearing a lower medial longitudinal arch contributes to the incidence of rearfoot pronation and thus increased plantar load on the medial aspect of the rearfoot [ 32 , 50 , 51 ]. Rearfoot valgus associated with a pronated foot often significantly increases the possibility of extensive foot pain [ 52 ].…”
Section: Discussionsupporting
confidence: 90%
“…Through the JC Mat built-in FPDS-Pro software (View Grand International Co Ltd., New Taipei City, Taiwan), both feet can be analyzed and qualified for parameters including AI, PPDs, centers of gravity, toe angles, and footprint characteristics. The repeatability and reproducibility of the device were demonstrated in previous studies [ 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Study participants were assessed using the JC Mat optical plantar pressure analysis device (View Grand International Co., Ltd., New Taipei City, Taiwan) and built-in FPDS-Pro software to determine the arch index (AI), plantar pressure distributions (PPDs), and balance of the foot centers of gravity [ 34 ]. The device has been proven repeatable and reproducible in previous studies [ 21 , 22 , 32 , 33 ]. The JC Mat uses the same principle and technology as the Harris footprint measurement.…”
Section: Methodsmentioning
confidence: 91%
“…However, these studies do not accurately reflect the plantar pressure distribution experienced by tennis players in their daily lives, and limited evidence has been reported regarding plantar pressure during normal gait. Given the above context, the study is based on a series of past experiences exploring the correlation between static and dynamic foot pressure profiles and lower extremity pain profiles in specific elite athletes [ 21 , 22 , 32 , 33 ]. On the basis of these findings, this study aimed at investigating the plantar pressure characteristics and foot posture of tennis players during their natural gait.…”
Section: Introductionmentioning
confidence: 99%